2023
DOI: 10.3390/molecules28030924
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Klf10 Attenuates Oxidative Stress-Induced Senescence of Chondrocytes via Modulating Mitophagy

Abstract: Osteoarthritis (OA) is the most prevalent degenerative joint disease in the elderly. Accumulation of evidence has suggested that chondrocyte senescence plays a significant role in OA development. Here, we show that Krüppel-like factor 10 (Klf10), also named TGFβ inducible early gene-1 (TIEG1), is involved in the pathology of chondrocyte senescence. Knocking down the Klf10 in chondrocytes attenuated the tert-butyl hydroperoxide (TBHP)-induced senescence, inhibited generation of reactive oxygen species (ROS), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Several known genes related to ARHL or senescence, including the forkhead gene family (comprising a diverse group of "winged-helix" proteins, e.g., Foxp1, Foxo1, Foxj1, Foxc1, and Foxg1) and the Adamts2, Arih2 (ariadne RBR E3 ubiquitin protein ligase 2), ACE2, Col13a1, and CDKN1C proteins, could be found among the genes predicted by motif-TF analysis (Fig. 3C and Table S8) [51][52][53][54][55][56]. In particular, the regulatory function of Foxg1 through the autophagy pathway during HC degeneration in presbycusis has been demonstrated in a previous study, and FOXG1 is considered a new molecular target for the treatment of age-related hearing loss [21].…”
Section: Discussionmentioning
confidence: 99%
“…Several known genes related to ARHL or senescence, including the forkhead gene family (comprising a diverse group of "winged-helix" proteins, e.g., Foxp1, Foxo1, Foxj1, Foxc1, and Foxg1) and the Adamts2, Arih2 (ariadne RBR E3 ubiquitin protein ligase 2), ACE2, Col13a1, and CDKN1C proteins, could be found among the genes predicted by motif-TF analysis (Fig. 3C and Table S8) [51][52][53][54][55][56]. In particular, the regulatory function of Foxg1 through the autophagy pathway during HC degeneration in presbycusis has been demonstrated in a previous study, and FOXG1 is considered a new molecular target for the treatment of age-related hearing loss [21].…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, co‐knockdown of KLF10 and Bcl2‐interacting protein 3 (BNIP3) resulted in a decrease in COL2A1 and LC3II/I and an increase in the expression of MMP13, p62, p16 and p21, as seen in the suppression of autophagic flux. This seems to indicate that KLF10 regulates autophagy by regulating the expression of BNIP3 107 . Moreover, another study reported that KLF10 overexpression accompanied by up‐regulation of Acvr1 gene expression and down‐regulation of Inhbb gene expression resulted in a significant reduction in chondrocyte proliferation and migration, promoting OA 108 .…”
Section: Role Of Klfs In Bone Diseasesmentioning
confidence: 93%
“…A recent study found that high expression of KLF10 was detected in human OA cartilage and mouse OA cartilage. 107 Notably, KLF10 was also up‐regulated in senescent chondrocytes. Down‐regulation of KLF10 not only restored the impaired mitochondrial autophagic flux, but also attenuated tert‐butyl hydroperoxide (TBHP)‐induced chondrocyte senescence by promoting mitochondrial autophagy, facilitated cell proliferation and inhibited senescence‐associated secretory phenotypes (SASPs), including the secretion of IL‐6, CXCL10, MCP1 and MMP3.…”
Section: Role Of Klfs In Bone Diseasesmentioning
confidence: 97%
See 2 more Smart Citations